Reversible scavenging and advection – Resolving the neodymium paradox in the South Atlantic. (1st December 2021) - Wang, Ruixue; Clegg, Josephine A.; Scott, Peter M.; Larkin, Christina S.; Deng, Feifei; Thomas, Alexander L.; Zheng, Xin-Yuan; Piotrowski, Alexander M.
Abstract: Significant gaps in our understanding of the oceanic cycling of neodymium (Nd) and the other rare earth elements (REEs) remain despite decades of research. One important observation which has not been adequately explained is that the concentration of dissolved Nd typically increases with depth, similar to nutrient profiles, while Nd isotopes appear to reflect conservative water mass mixing in the intermediate and deep ocean; this has been termed the "Nd paradox". Here we present a detailed study of the dissolved Nd isotopic composition across a section at 40°S in the South Atlantic, collected by UK GEOTRACES cruise (section GA10). The South Atlantic represents a natural laboratory for our understanding of spatial controls on ocean geochemistry, because of the large variability of inputs, spatial differences in particulate cycling, and horizontal advection and mixing at depth between major northern- and southern-sourced water masses. This variability has also made the South Atlantic a critical region subject to intense investigations that aim at reconstructing past changes in ocean processes, such as changes in biological productivity and deep ocean circulation. Our Nd isotope results from the GA10 section provide observational data show the signal of water mass mixing and reversible scavenging. In the surface ocean (0–600 m), Nd isotopic compositions are distinct between different surface ocean currents and spatially can be tied to various continental sources. In the intermediate ocean (600–2500 m), the vertical Nd isotope distribution exhibits distinct signals of different water masses by horizontal advection, including upper North Atlantic Deep Water and Antarctic Intermediate Water formed in the Atlantic Ocean or the Indian Ocean. The Nd isotope distribution also reflects influence of reversible scavenging that smears the signals downwards in the water column (i.e., offset to more radiogenic values). In the deep ocean below 2500 m, Nd isotope distribution largely follows conservative water mass mixing model. Nd concentration in the deep ocean, however, deviates from conservative mixing and increases constantly with depth. We also observe that Nd isotopes appear to be shifted towards the composition of overlying water masses. These observations suggest that reversible scavenging of Nd onto organic and other types of particles is a major vertical process throughout the water column. We also suggest that this process can resolve the "Nd paradox" of decoupling of Nd concentration and isotopic composition due to mixing dynamics. Because abyssal water masses already have a high Nd concentration, a given amount of Nd added from the vertical process has less of an effect on Nd isotopic compositions in deep water masses than it does for intermediate water masses which have comparatively low Nd concentration.